The impact of traditional market relocation on the sellers at Dinoyo Market in Malang. - susi lowati (Jurnal VOK@SINDO, 2015)
This study aims to know and explain perception of the sellers at Dinoyo market about the location of garbage dump (TPS) in Merjosari; the impact of the traditional market relocation in garbage dump in Merjosari on the sellers; whether the market relocation has any relationship with the sellers’ income, the good prices, the number of the workers; as well as the variabels which have dominant relationship with the traditional market relocation in garbage dump (TPS) in Merjosari. This study employed survey method. The data analysis was done by using Chi-square (X²) and SPSS. The object of this study is the sellers in traditional market in Dinoyo Malang. The findings show that the sellers consider the new market place in Merjosari is not strategic, the relocation has decreased the sellers’ income and increased transportation fee, the relocation has no relationship with the good prices and the number of the workers, and there is novariabel which has dominant relationship with the the relocation of Dinoyo market sellers in garbage dump (TPS) in Merjosari.